2009
DOI: 10.1089/jwh.2008.1138
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Screening: Factors Associated with Bone Mineral Density Testing of Older Women

Abstract: Consideration of factors associated with BMD testing may be useful in developing interventions to increase osteoporosis screening rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Considering the existing focus on the risk of underweight individuals for osteoporosis, it comes as no surprise that the rate of DXA screening declines as BMI increases. (69) This is likely to be due to a combination of provider and patient inattention to fracture as a legitimate health risk. The challenge is to devise fracture risk detection approaches that recognize the relatively lower risk of fractures in those with high BMI with the need to reduce the personal and population burden of their fractures.…”
Section: Bone Density Testing In Overweight and Obese Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the existing focus on the risk of underweight individuals for osteoporosis, it comes as no surprise that the rate of DXA screening declines as BMI increases. (69) This is likely to be due to a combination of provider and patient inattention to fracture as a legitimate health risk. The challenge is to devise fracture risk detection approaches that recognize the relatively lower risk of fractures in those with high BMI with the need to reduce the personal and population burden of their fractures.…”
Section: Bone Density Testing In Overweight and Obese Individualsmentioning
confidence: 99%
“…(75) Comorbidities that are more frequent in obese people may also play a role in a lower frequency of screening. (69,73) While DXA screening is one area of focus, screening among overweight and obese populations for low and declining physical function, fall risk, and insufficiency of vitamin D and other nutrients may have even greater returns in improving not just bone health but also mobility and quality of life.…”
Section: Bone Density Testing In Overweight and Obese Individualsmentioning
confidence: 99%
“…As such, our cohort differs from administrative cohorts based on BMD testing. Prevalence of BMD testing varies significantly across geographical areas, socioeconomic status, and age (27)(28)(29)(30). BMD-based cohorts often consist of younger and healthier individuals, thus underestimating FF rates in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…studies that also found low rates of BMD screening in at-risk women. 21,22 Given the high level of morbidity and mortality associated with osteoporotic fracture, it is unfortunate that compliance with screening recommendations is so low. This is especially true for women who have already experienced a fracture, because this is a readily identifiable risk factor and places these women at particularly high risk for a subsequent fracture.…”
Section: Discussionmentioning
confidence: 99%